Sodre and the Dialectics of Brazil's Social Formation - Del Roio, Marcos [UNESP] (2019)
In the early 1960s, Nelson Werneck Sodre developed a complex and sophisticated theory of Brazilian reality and its historical dynamics. In the light of the criticism and distortion of his views of the intervening years, a clarifying summary of his most important work is in order. Such a summary suggests that the new absolute truths of Brazilian historiography and political sciences have elements that can be questioned and that in interpretations of Brazil one can never forget that science is also expressed as ideology and political practice.